Estudio de la emisión polínica de un cultivo de girasol (Helianthus annuus L. ) (Semiárida, 2020)
The objective of this study was to estimate the pollen emission dynamics of the sunflower crop and its relationship with some environmental variables such as daily mean temperature (DMT) and precipitation. Two sunflower hybrids (ACA 884 and Cargill 5515) were sown under field conditions at the Facultad de Agronomía, La Pampa on 26/10/98. Meteorological data was obtained from an agrometeorological station located near the field experiment. Soil water content was measured al sowing time and its dynamic registered over time. Capitula population in the crop was measured before first anthesis took place. During the anthesis period the number of disc florets per capilulum was counted in randomly selected plants. To measure the production ot pollen grains per flower, florets still closed were taken from sectors of the capitula located at its periphery, middle and center. DMT controlled the flowering progress of both genotypes according with the maintenance or not of its value over the average temperature during the whole process. The total floret number was similar for both hybrids and the concentration of pollen grains per floret showed no difference between hybrids. Significant differences were however found between the sectors of the capitulum, being the peripheral one the most productive.Resúmenes de Trabajos presentados en otras publicaciones (por docentes de la UNLPam.) Presentado en VII Jornadas Pampeanas de Ciencias Naturales, 1-3 de diciembre de 1999. Santa Rosa. La Pampa: 105-113.